Modified shouldice repair of bilateral inguinal hernia with hydrocele: A case report (South East Asia Journal of Public Health, 2017)
Indirect inguinal hernia is a common medical condition that can be caused by an embryological defect due to failure of closure of processus vaginalis that can lead to herniation (i.e. abnormal protrusion) of abdominal contents into scrotal sac in males. In this paper, we describe an interesting case report of a patient with bilateral inguinal hernia with hydroceles who underwent a modified shouldice repair. In addition, we also discuss initial presentation & surgical management of this patient who had painless postero-inferior displacement of testes. Reason why we think this case is unique, is because of ‘bilateral’ hydroceles along with bilateral inguinal hernia which is rarely seen as compared to its unilateral counterparts. We also describe various surgical steps of modified shouldice repair with bilateral orchiopexy along with the post-operative outcome. Finally, we also discuss various types of hydroceles, along with its pathology that is found after surgical resection.South East Asia Journal of Public Health Vol.7(1) 2017: 62-65